Kepemilikan Saham oleh Buruh sebagai Upaya Penegakan Sistem Ekonomi Pancasila - Wahyudi, Epri (University of Jember, 2017)
This article discusses the conceptual idea in addressing the situation of workers in Indonesia who are perceived not to have the right to prosper in the work already owned. In economics, labours play an important role because they are the wheels in driving the production of goods and services. The unfilled labour rights to live prosperous is caused by the absence of their authority to contribute in determining a policy within a company. To overcome the imbalance of bargaining position between workers and employers, a regulation or policy is required to materialise access to share ownership within the company. By owning shares, workers have the right to convey ideas in determining company policy. In addition, labours will also easily access all company information including company report approval. It concludes that the ownership of shares by labours in the company is a necessity and an effort to realise Pancasila Economic System in order to fulfil the more substantive labour rights. Keywords: Share Ownership, Labours, Pancasila Economic System